2020
DOI: 10.29019/enfoqueute.v11n4.652
|View full text |Cite
|
Sign up to set email alerts
|

Mass trapping of Pectinophora gossypiella (Saunders) (Lepidoptera: Gelechiidae) using light and sex-pheromone traps in cotton

Abstract: The pink bollworm, Pectinophora gossypiella (Saunders) (Lepidoptera: Gelechiidae) is an important insect pest of the cotton crop worldwide. Sex-pheromone and light traps were used to monitor the adult P. gossypiella population in Bt cotton field for the years 2017-18 at southern Punjab, Pakistan. The sampling of infested bolls was done to record the damage level of P. gossypiella. The sex-pheromone traps captured approximately 2-3 times more adults than light traps in all locations during 2017-18. For sex-phero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Pheromones have been demonstrated to be effective for mass trapping and disrupting the mating of specific insect pests. Pheromone trapping, either alone or in combination with bio-rational spraying, has been reported to conserve natural enemies and control various insect pests, including eggplant fruit and shoot borer (Leucinodes orbonalis Guenee), and cotton bollworm (Helicoverpa armigera) in Bangladesh [20][21][22][23][24][25]. The use of pheromone traps is also viewed as a viable option for controlling insect pests and reducing the use of synthetic insecticides in worldwide vegetable production [15,18,22,23,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pheromones have been demonstrated to be effective for mass trapping and disrupting the mating of specific insect pests. Pheromone trapping, either alone or in combination with bio-rational spraying, has been reported to conserve natural enemies and control various insect pests, including eggplant fruit and shoot borer (Leucinodes orbonalis Guenee), and cotton bollworm (Helicoverpa armigera) in Bangladesh [20][21][22][23][24][25]. The use of pheromone traps is also viewed as a viable option for controlling insect pests and reducing the use of synthetic insecticides in worldwide vegetable production [15,18,22,23,25].…”
Section: Introductionmentioning
confidence: 99%
“…Pheromone trapping, either alone or in combination with bio-rational spraying, has been reported to conserve natural enemies and control various insect pests, including eggplant fruit and shoot borer (Leucinodes orbonalis Guenee), and cotton bollworm (Helicoverpa armigera) in Bangladesh [20][21][22][23][24][25]. The use of pheromone traps is also viewed as a viable option for controlling insect pests and reducing the use of synthetic insecticides in worldwide vegetable production [15,18,22,23,25]. Studies have suggested that the dependency on insecticides can be reduced by 35% to 50% without reducing the yield of the product by adopting pheromone traps [26,27].…”
Section: Introductionmentioning
confidence: 99%